Fine-Needle Aspiration Cytology of Extramedullary Plasmacytoma: A Six-Year Case Series - Jain, Tripti; Singh, Surinder; Narayanan, Arsha; Kumari, Sujata; Chhabra, Harinder Singh (Annals of Pathology and Laboratory Medicine, 2025)
Background: Due to its cytomorphological overlap with lymphoma or metastatic carcinoma and its protean anatomic distribution, extramedullary plasmacytoma (EMP), which accounts for less than 5% of plasma cell neoplasms, usually presents a diagnostic problem. Timely staging and treatment depend on early cytological identification. Materials and Methods: We retrospectively reviewed 8 cases of extramedullary plasmacytoma (EMP) diagnosed on fine needle aspiration cytology (FNAC). Clinical history, imaging, laboratory data, treatment, and follow-up were retrieved from hospital records. FNAC smear samples were assessed. Cell blocks were prepared in all 8 cases and subjected to immunocytochemistry for CD138, CD38, CD45, and Ki-67 markers. In situ hybridization for κ and λ light chains was done in all cases. Descriptive analysis was performed given the small sample size. Results: Eight patients (mean age 70.3 years; M:F=5:3) presented with solitary soft tissue masses ranging from 2.8 to 6.5 cm. Sites included paranasal sinus (2), axilla (1), breast (1), sternum (1), orbit (1), scapula (1), and subcutaneous thigh (1). FNAC smears showed a spectrum from mature plasma cells to plasmablast-rich populations. Immunocytochemistry revealed monotypic κ-restriction in five cases and λ in three. Over a median follow-up of 15.5 months, five patients remained disease-free, two progressed to multiple myeloma, and one was lost to follow-up. Conclusion: FNAC, combined with light-chain assessment and meticulous clinico-radiological correlation, is a rapid and reliable modality for diagnosing EMP even in resource-constrained settings. Recognizing plasmablast-rich patterns is essential because they herald aggressive behavior and a higher risk of progression to myeloma.